A wideband dual-polarized patch antenna fed with the aperture-coupled microstrip. Issue 1 (2nd January 2018) - Zhao, Fengxian; Zhang, Wenmei; Han, Liping; Han, Guorui; Yang, Rongcao
ABSTRACT: In this paper, a compact broadband dual-polarized stacked patch antenna with the aperture coupled microstrip feed is proposed. By adding a parasitic disc patch, the bandwidth is effectively broadened. Meanwhile, to improve the isolation at the low frequency band, a rectangular slot is etched along the diagonal line of the ground plane. The measured results show that the proposed antenna can operate from 9.6 to 22.4 GHz and the relative bandwidth is 80%. Also, the isolation within the operating frequency band is better than 15 dB and the maximum gain reaches 4.08 dBi.